Unveiling the Challenges of Knowledge Management in Global Enterprises: An Exploratory Study - Yessica Amelia; Eri Kusnanto; Ngadi Permana (LPPM STIE Kasih Bangsa, 2024)
This qualitative study aims to investigate the challenges encountered in knowledge management within global enterprises. The research employs a qualitative research model to delve into the intricacies of knowledge management practices. Sampling techniques involve purposive sampling to select participants with expertise in knowledge management across diverse global enterprises. Data analysis utilizes thematic analysis to identify recurring patterns and themes within the collected qualitative data. The findings reveal multifaceted challenges such as cultural differences, technological limitations, and organizational complexities in implementing effective knowledge management strategies within global contexts. This study contributes to a deeper understanding of the nuances associated with knowledge management in multinational organizations, offering insights for practitioners and academics alike.